(untitled) (Revista Ciência Agronômica, 2015)
The consumption of reduced-calorie cakes has been increasing, however this has presented challenges to be overcome concerning the formation of their structure when the sucrose is substituted by alternative sweeteners, gums or thickening agents. The present study evaluated the internal characteristics of cakes with a reduction in sucrose, and the effects of its substitution on starch gelatinisation. Starting with a pre-established formulation, the sucrose was gradually substituted by a 1.0% mixture of sucralose in a 1.5% xanthan gum solution. In the substituted cake mix, the apparent viscosity and its thermal properties were evaluated using differential scanning calorimetry (DSC). Specific volume (SV) and cell count (CC) were evaluated in the cakes. As the sucrose content decreased (52.17 to 10.00%), the specific volume (1.94 to 0.7 mL/g), cell count (36.2 to 4.0 cell/cm²) and the apparent viscosity of the batter (337.56 to 631.40 cP) were also reduced. The results showed that substituting the sucrose contributed greatly to the formation of defects in the cake structure (holes). From the data obtained, and thermograms of standard cake batters and those with a reduction in sucrose, it can be concluded that sucralose reduced the temperature of starch gelatinisation, speeding the process and causing compaction of the cake structure during baking, favouring the formation of bubbles throughout the batter.